Study of risk factors in patients with postpartum hemorrhage- an observational study - Uthpala, V.; Gracelyn, J. Leila (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2022)
Background: In both developed and developing countries, postpartum haemorrhage (PPH) can occur in 1-5% of deliveries, and it is still the leading cause of maternal morbidity and mortality. Clinicians must be aware of PPH risk factors and should consider them when counselling women about where to birth. The goal of this study was to assess risk factors in patients with postpartum hemorrhage. Methods: This study comprised 50 pregnant patients with PPH. Their maternal age, parity status, GA, and mode of delivery were recorded. Other associated co-morbidities with PPH such as anaemia, H/O LSCS, hypertensive status, abruptio placentae, premature rupture of membranes, and prolonged labour were also recorded. The morbidity rate and intervention employed were also recorded. Results: In the present study, significant risk factors for PPH were 20-24 years of age, primipara, severe anaemia (Hb<7 gm%), previous LSCS, hypertensive disorders of pregnancy, premature rupture of membranes, abruptio placentae and prolonged labor. Conclusions: Monitoring these identified risk factors could enable extra vigilance during labor, and preparedness for managing PPH in all women giving birth